Gastroschisis in Finland 1993 to 2014-Increasing Prevalence, High Rates of Abortion, and Survival: A Population-Based Study - Raitio A; Lahtinen A; Syvänen J; Kemppainen T; Löyttyniemi E; Gissler M; Hyvärinen A; Helenius I (My University, 2022)
Introduction The study aims to assess the changes in prevalence and mortality of gastroschisis, and to identify associated anomalies.
Materials and Methods It is a population-based nationwide study. All gastroschisis cases were identified in the Finnish Register of Congenital Malformations and the Care Register for Health Care from 1993 to 2014 including live births, stillbirths, and terminations of pregnancy due to fetal anomalies. Associated anomalies were recorded, and analyzed, and prevalence and infant mortality were calculated.
Results There were 320 cases of gastroschisis; 235 (73%) live births, 16 (5%) stillbirths, and 69 (22%) terminations of pregnancy. Live birth prevalence of gastroschisis in Finland was lower than generally reported (1.73 in 10,000). However, due to relatively high rates of abortion, our total prevalence of 2.57/10,000 was similar with other reports. The most common risk factor was young maternal age. Babies with gastroschisis were born prematurely, on average on the 36th week and most are delivered by caesarean section. There was a significant increasing trend in live birth prevalence (p = 0.0018). Overall infant mortality was 7.7% (18/235), 7.2% (16/222) in simple gastroschisis and 15% (2/13) in complex gastroschisis. Associated anomalies were rare both in aborted fetuses and neonates, and there was only one case with a chromosomal abnormality.
Conclusion Gastroschisis is usually an isolated anomaly with increasing birth prevalence and excellent survival rates. Regardless of the good prognosis, the abortion rates in Finland are higher than previously reported, and we hypothesize this to be due to lack of appropriate antenatal counselling.